ANALISIS PERWATAKAN TOKOH UTAMA DALAM NOVEL SEPATU DAHLAN KARYA KHRISNA PABICHARA - Mardiana Buulolo (Universitas Nias Raya, 2025)
The background of the problem in this study is the character of the main character because the researcher is interested because the depiction of the character shown by the character in this novel is very lacking in economy, different from today's life. The purpose of this study was to describe the character in the novel Sepatu Dahlan by Khrisna Pabichara. The method used in this study is qualitative research method with a descriptive approach. The character in the novel Sepatu Dahlan by Khrisna Pabichara is confident, responsible, and wise. In the novel Sepatu Dahlan by Khrisna Pabichara, there is a character that is confident, there is. 5 citations, the insured 5 citations, and wisely there are 6 citations. In total, there are 16 citations in the research data. Based on the results of the study, the researcher suggested 1) It is fitting that the description in this paper is not just scientific criticism for researchers and readers, but can provide scientific wisdom and can be used as valuable lessons in addressing problems in life. 2) The researcher advises the reader to apply it to everyday life. 4) May this study motivate readers to examine other aspects of other novels as a motivation. If necessary, students of the Indonesian Language and Literature Education study program should empower this kind of study as a form of appreciation activity.